Contact Force Models for Multibody Dynamics - Flores, Paulo; Lankarani, Hamid M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book analyzes several compliant contact force models within the context of multibody dynamics, while also revisiting the main issues associated with fundamental contact mechanics. In particular, it presents various contact force models, from linear to nonlinear, from purely elastic to dissipative, and describes their parameters. Addressing the different numerical methods and algorithms for contact problems in multibody systems, the book describes the gross motion of multibody systems by using a two-dimensional formulation based on the absolute coordinates and employs different contact models to represent contact-impact events. Results for selected planar multibody mechanical systems are presented and utilized to discuss the main assumptions and procedures adopted throughout this work. The material provided here indicates that the prediction of the dynamic behavior of mechanical systems involving contact-impact strongly depends on the choice of contact force model. In short, the book provides a comprehensive resource for the multibody dynamics community and beyond on modeling contact forces and the dynamics of mechanical systems undergoing contact-impact events.
1. Introduction,- 2. Pure Elastic Contact Force Models -- 3. Dissipative Contact Force Models -- 4. Multibody Systems Formulation -- 5. Numerical Methods in Multibody Systems -- 6. Demonstrative Examples of Application.
Keywords: Mechanical engineering; Multibody systems; Vibration; Mechanics, Applied; Mechatronics; Biomedical engineering; Mechanical Engineering; Multibody Systems and Mechanical Vibrations; Mechatronics; Biomedical Engineering and Bioengineering